2023
DOI: 10.1371/journal.pone.0278455
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of keratoconus: Two numerical studies

Abstract: Background The steep cornea in keratoconus can greatly impair eyesight. The etiology of keratoconus remains unclear but early injury that weakens the corneal stromal architecture has been implicated. To explore keratoconus mechanics, we conducted two numerical simulation studies. Methods A finite-element model describing the five corneal layers and the heterogeneous mechanical behaviors of the ground substance and lamellar collagen-fiber architecture in the anterior and posterior stroma was developed using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…It has been proposed that the focal weakness is the initiating event in KC, resulting in a cycle of biomechanical decompensation with increased strain and thinning in the weak area, leading to a focal increase in stress [ 57 ]. In addition, as a risk factor for KC, vigorous eye rubbing was shown sharply increased force to corneas [ 58 ]. In our previous studies, we found that mechanical stretch could induce the expression of the hub genes including IL6 [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that the focal weakness is the initiating event in KC, resulting in a cycle of biomechanical decompensation with increased strain and thinning in the weak area, leading to a focal increase in stress [ 57 ]. In addition, as a risk factor for KC, vigorous eye rubbing was shown sharply increased force to corneas [ 58 ]. In our previous studies, we found that mechanical stretch could induce the expression of the hub genes including IL6 [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…One might interpret these results as evidence that the entire cornea weakens in keratoconus, but this interpretation is flawed since none of the methods were able to assess asymmetry. Finite element modeling has identified loss of tissue stiffness, which is localized to a concentric area, as a contributor to keratoconus progression [ 30 ], and several groups have used Brillouin microscopy, a form of non-destructive optical elastography [ 31 ], to demonstrate focal, not global, weakness in keratoconus that is associated with local corneal thinning and steepening [ 32 34 ]. In other words, there is an asymmetry in corneal biomechanical parameters, relative tissue weakness adjacent to relative tissue strength, which is typically not accounted for in their clinical assessment of keratoconus.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent literature, an exception to this common way to proceed is represented by an interesting study on the biomechanics of the keratoconus, where the authors model the thin layers with the goal to capture the conditions that lead to the formation of a conus in a diseased cornea [10]. Regrettably, the selection of the material properties of the thin layers is not commented or justified; also the discretized finite element model adopted in the numerical simulation is not shown.…”
Section: Discussionmentioning
confidence: 99%